Dialyzer reuse; effect on efficiency and biocompatibility - Huzayin, Atef H; El Aggan, Hayam A; Rizk, Mohamed M; El Koraei, Ahmed F (African Journal of Nephrology, 2016)
Fifteen patients on maintenance haemodialysis were studied before and after reuse of cuprophane hollow-fiber dialysers to assess its biocompatibility and efficiency. There was a significant increase in hematocrit value and hemoglobin level by the end of dialysis. Also, there was a significant decrease in total leukocyte (neutrophilic & eosinophilic) and platelet counts with a peak at 15 minutes after the start of dialysis, then there was a gradual increase till the end of dialysis reaching near the predialysis value. These changes occurred both in the first use and the reuse sessions. The decrease in the neutrophilic count with the reused dialyzer was significantly less compaired to first use dialyzer. The terminal complement complex (TCC) significantly increased and reached its maximum after 15 minutes, then it began to decline till the end of the dialysis. Similarly, these changes were significantly less in the reuse dialyzers. No correlation was found between the changes of the TCC and the decrease in different cellular elements. There was an increase in plasma bicarbonate and pH by the end of dialysis. Also, hypoxia and hypocapnea occured shortly after the start of dialysis session with acetate dialysate, but they returned to their predialysis values at the end of both dialysis sessions. This can be attributed to the loss of carbon dioxide into the dialysate with subsequent hypoventilation. The clearances of urea, creatinine and phosphorus showed insignificant difference between the new and reused dialyzers at zero and 4hr time with significant decrease by the end of dialysis in both dialysis session. This could be explained by keeping the surface area of the reused dialyzers within the acceptable values (80-100%) of the first use dialyzer. It can be concluded that reused dialyzers were to some extent more hemocompatible than the first use dialyzers. Complement activation is not the sole factor for the biocompatible reactions during dialysis. Reuse of dialyzers can be a safe procedure by adopting appropriate sterilization, reprocessing and storage techniques and limited number of reuse.